The Origins of the Women's Movement in the Philippines and Thailand: A Preliminary Comparison - Jose, Mary Dorothy dL.; Alfaro, Ma. Rita Lourdes A. (Review of Women's Studies, 2023)
This paper traces the burgeoning of the women's movement in two ASEAN countries - the Philippines and Thailand, chosen for their distinctive colonial experiences. It endeavors to identify commonalities and dissensions in the history of their fight for women’s rights and further looks at the direction taken by the respective women's movements that emerged in these two countries. In carrying out this aim, this research investigates how distinctive colonial experiences shaped the origins of these countries' women's movements. Utilizing the transnational feminist approach, this study analyzes particular contexts and dynamics in the region that helped shape the direction of women's fight for a better place in society, taking into consideration nationality, class, religion, and region as important variables. It provides the context to the origins of the women's movement in the Philippines and Thailand from pre-colonial times for the Philippines and from the pre-1932 period for Thailand up until 1945 at the end of World War II. A preliminary comparison is done, focusing on the different factors that influenced the beginnings of the women's movement in both countries, the role of the market economy in providing different experiences for women from different classes, the struggle for gender equality through religious feminism, and how the attainment of women's political rights in the 1930s affected women's participation in politics. Spurred, moreover, by the aim of affording recognition to women who transcended societal limitations, this research underscores the struggles of Filipino and Thai women in forging the path of the women's movement in their respective countries. It enjoins academics to undertake topics that will highlight women's role in history and supplement the gaps within comparative studies of women in ASEAN nations.